5-year experience in the diagnosis and treatment of occult urinary incontinence in women with pelvic organ prolapse. (March 2017) - Karamustafaoglu Balci, Burcin; Gungor Ugurlucan, Funda; Yasa, Cenk; Yalcin, Onay
Abstract: Objective: Our aim was to analyze our five-year experience in the diagnosis and treatment of occult urinary incontinence in women with pelvic organ prolapse. Study design: The medical records of all patients who were admitted to the Division of Urogynecology of Istanbul Faculty of Medicine between January 2008 and December 2013; in total, 1600 patients were retrospectively evaluated. The study population included 287 patients who had prolapse beyond the hymen and underwent two consecutive urodynamic studies with and without prolapse reduction. Demographic data, medical records, physical examination, full urogynecologic examination, urodynamic investigations, treatment modality, the results of the treatment and King's Health Questionnaire scores before treatment and at one-year follow-up were recorded. Results: Eighty-five of 287 patients (29.6%) were continent, 20 (23.5%) of whom had occult stress urinary incontinence during cystometry. Among these 20 patients, 17 underwent anti-incontinence surgery; 12 were satisfied with their surgery and had no postoperative urinary leakage. Twenty (23.5%) patients had overactive bladder symptoms during urodynamic studies after prolapse reduction. King's Health Questionnaire scores before and after the operation, showed that health status of 12 patients was better, 1 patient was unsatisfied after the treatment, 2 patients' scores did not change and 2 patients were lost to follow up. Conclusions: In conclusion, the prevalence of occult urinary incontinence was 23.5% when using urodynamics with prolapse reduction. 12 of the 17 patients diagnosed with occult urinary incontinence were satisfied with surgery and had no postoperative urinary leakage.